PERANCANGAN SISTEM INFORMASI BERBASIS ORIENTASI OBJEK MENGGUNAKAN STAR UML DI CV NIASA BANDUNG - Nova Indrayana Yusman (Jurnal Accounting Information System (AIMS), 2018)
In terms of data processing information, in NIASA CV there is no permanent systemyet, did not use any application like Microsoft Excel and others. For the size of a company, according to the author's observations there are many weaknesses, and the system used so far is only the result of the calculation of the purchase of raw materials and the sale of finished goods. The report also took a long time to record it because there is no bookkeeping.In this design system using the method of survey in the collection and processing of data information to contain a picture of the situation in place of research object.  As for system design, the author uses Unified Modeling Language (UML). UML it self are one of many tools under Object Oriented Programming, so safe to assume that Star UML will be the right tool for analyze. The design is now expected to facilitate users in reporting and the owners of  Niasa CV can view or collect reports easily, quickly, and probably help the CV to have a permanent system.